HIP ARTHROSCOPY: WEST OF SCOTLAND EXPERIENCE. Issue 17 (24th October 2013) - Akhtar, MA; Campton, L
Abstract : Hip arthroscopy has evolved over the last decade. There had been an increase in the demand for hip arthroscopies from patients and their general practitioners due to available information and better diagnostic modalities like Magnetic resonance Arthrography. The senior author has performed 132 hip arthroscopies since 2010. This study was performed to reflect on our experience of hip arthroscopies to improve our practice. Data was collected prospectively between June 2011 and May 2013 for all patients undergoing Hip arthroscopy at Gartnavel General Hospital under the care of a specialist Hip surgeon. Demographics details, diagnosis of hip or groin pain, operative findings and surgical treatments performed were recorded for 49 patients. The mean age was 31 years (range 17–61). 57% patients were male and 43% female. 59% had right and 41% had left sided hip pathology. The diagnosis of hip pain following arthroscopy was Femoroacetabular Impingement and Labral tear in 67% patients, Femoroacetabular Impingement in 8%, isolated labral tear in 6%, Osteoarthritis in 16% and no intraarticular cause of hip pain was found in 2%. The site of Femoroacetabular impingement was anterior in 86% patients, anterolateral in 11% and lateral in 3% patients. The mean angle was 88 degrees of hip flexion for impingement (range 60–110). 75% patients had reduced anterior head and neck offset. The size of the labral tear was <5 mm in 11% patients, 5–10 mm in 8%, 10–15 mm in 23%, 15–20 mm in 37% and 20–25 mm in 20% patients. In our study cohort 67% patients had Femoroacetabular impingement and an associated labral tear which required treatment. 80% of patients had a tear of >10 mm in size. 16% of patients in our cohort had osteoarthritis changes which were not amenable to arthroscopic treatments. This reflective practice can help surgeons to improve patient selection for hip arthroscopy which can also result in improved outcomes following this procedure.